THE EFFECT OF SHIFT WORK SYSTEM AND FATIGUE TOWARDS EMPLOYEE STRESS AT ASTON MANADO HOTEL - Mamengko, Rosita Julianda; Saerang, David P. E.; Saerang, Regina T. (Universitas Sam Ratulangi, 2020)
Human Resources is one of the most important parts of a company, also it has a role to regulate all obligations, regulations and discipline of the workers. Aston Manado Hotel is the object of this study. The purpose of this study is to determine the level of influence of stress on employees from the applied shift work system and fatigue to employees who worked shifts on the object. The method used in the study is multiple linear regression using saturation sampling technique taking 57 respondents who worked in shifts. The result of the study using a questionnaire showed that shift work system provides a positive and significant effect on employee stress as well as fatigue gives a significant effect on employee stress, and also shift work system and fatigue had a relationship so that it shift work system and fatigue significantly affected stress on employees. As a recommendation, this research can be a description, input and reference for other researcher, companies and work institutions that apply shift work systems to their employeesÂ keywords: shift work system, fatigue, employee stress